Learning to read the complex Manchu writing system: a mixed methods study of novice learners in a Chinese university - Li, B (2022)
This study investigated the association between the Manchu writing system and novice learners’ uju symbol block decoding performance. The Manchu writing system was examined on two parameters: visual complexity of Manchu symbols and mapping complexity between symbol and sound. Designed as mixed methods research, this study randomly selected undergraduate students (n = 196) in a Chinese university, who were given Manchu uju naming tasks in Test 1 on visual complexity and Test 2 on symbol–sound mapping complexity. Moreover, the instruction on Manchu orthographic knowledge was observed. Theoretically, an area of interest in reading acquisition is the learning about the visual features of a writing system. Symbol visual complexity was previously found to be negatively associated with word reading in a limited number of orthographies such as Kannada (Nag, Snowling, Quinlan, & Hulme, 2014), Arabic (Abdelhadi, Ibrahim, & Eviatar, 2011) and Chinese (Yu, Zhang, Priest, Reichle, & Sheridan, 2018). To measure visual complexity, the present study adopted a multidimensional framework which included pixel count (Nag & Snowling, 2012), perimetric complexity, the number of simple features, the number of connected points and the number of disconnected components (Chang, Chen, & Perfetti, 2018). Results of Test 1 showed that visual complexity significantly and positively associated with participants’ uju decoding performance measured by error rate and reaction time. Furthermore, connected point was identified by multiple linear regression as the unique predictor for decoding accuracy, and connected point and disconnected component were found to predict decoding speed. Results of Test 1 suggested that novice readers may use connected point to identify features in visual processing of uju symbol blocks. Secondly, as Manchu orthography is characterized by the complex mixed mapping between symbol and sound (Nag, 2007, 2017a, 2021), it remained unknown what symbol grain size(s) (Ziegler & Goswami, 2005) was/were adopted in Manchu reading. Results of Test 2 showed that participants’ decoding performance was not significantly different when uju were provided in the manipulated “mixed” and “blocked” condition. Yet, their performance was more accurate and rapid in naming uju with all comprising phoneme markers in one-to-one mapping with sound than those containing a target marker in one-to-multiple mapping with sound. The results suggested that phoneme marker may be used for Manchu symbol blocks processing. This finding on learners’ choice of the smaller grain size phoneme marker in reading must be seen in the context of the classroom observations on Manchu orthographic knowledge instruction. Although both global and analytic strategies as defined by Nag (2011, 2017a, 2017b) were applied by the teacher in instruction of the uju symbol blocks, even novice learners who received a rather limited ten sessions of Manchu instruction on the orthography were found to be reading analytically by decomposing an uju into component phoneme markers. Finally, in line with theorizing by Nag, this study posits that reading Manchu symbol blocks requires intra-symbol processing, which involves (a) at the feature level, identification and configuration of visual features into phoneme markers, and (b) at the symbol level, conversion of phoneme markers into sounds.